Resolusi Konflik Gerakan Nasional Penyelamatan Sumber Daya Alam: Lintasan Gagasan, Praktik, dan Bentang Masalah - Cahyono, Eko; Sulistyanto, Sulistyanto; Azzahwa, Sarah (Komisi Pemberantasan Korupsi, 2019)
The conflict resolution is one of the mandatory requirements to expand and to actualize the people's sovereign territory in the name of the sovereignty and justice of the people's living space. The implementation process is still leaving some lessons of learning and challenges in the future, both internal and external factors. For these reasons, the future recommendation and agenda are building the political seriousness of the state, strengthening the regulation of conflict resolution and its authoritative institutions, enforcing of people's sovereignty areas, limiting the size of ownerships of land tenure and agrarian sources, and creating a policy breakthrough.